Fluorescent Determination of Glucose Using Silicon Nanodots. (12th December 2018) - Chen, Chaohui; Zhang, Yanan; Zhang, Zhengtao; He, Rongxiang; Chen, Yong
ABSTRACT: Here is reported a fluorescent biosensor for glucose detection based on water-soluble and pH-responsive silicon nanodots. The silicon nanodots were prepared using a facile hydrothermal method. The advantages of using the silicon nanodots as glucose sensor are twofold. Firstly, the fluorescence of silicon nanodots was quenched by hydrogen peroxide that was produced from glucose oxidation. Secondly, the fluorescence of silicon nanodots was highly sensitive to gluconic acid that was also produced by glucose oxidation. Our results show that this method detected glucose as low as 0.54 µM with a good selectivity and allowed the determination of glucose in serum samples. This method is also simple, rapid, low-toxic and low-cost, thereby hold high application potential for biological assays.